The Effect of Application of the ARCS Learning Model (Attention, Relevance, Confidence, Satisfaction) on Motivation - Meirisa Sahanata; Fitri Kumala Dewi (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2022)
This study aims to determine the students' motivation to learn mathematics by applying the ARCS learning model. This type of research is quantitative research, with an experimental approach. The research design used in this study is the Randomized Control Group Design. The sample in this study was class VIIA as the experimental class and class VIIB as the control class. Based on initial observations, it was found that students' learning motivation was still relatively low. Efforts to overcome these problems can be through the use of learning models that are in accordance with the characteristics of students' problems in this case applying the ARCS learning model (Attention, Relevance, Confidence, Satisfaction). The results showed that the data on the percentage of students' learning motivation questionnaires for each aspect in the control class, for students' Attention conditions to learning mathematics was 51.51%, students' Relevance conditions were 49.31% and for Confidance. Students in learning mathematics is 50.22% while student satisfaction in learning mathematics is 51.36%, so that the average score is 50.77%. The data obtained on the percentage of students' learning motivation questionnaires for each aspect in the experimental class, for the condition of students' Attention to learning mathematics by 72.38%, students' Relevance conditions of 75.47% and for Confidance students in learning Mathematics is 79.52% while students' satisfaction in learning mathematics is 77.30%. The average score of the experimental class is 75.90%. It can be concluded that the ARCS learning model (Attention, Relevance, Confidance, Satisfaction) can affect the mathematics learning motivation of class VII students with a comparison of the average score of students' mathematics learning motivation in the experimental class which is higher than the average score in the control class, which is 75.90 % > 50.77%.